Effect of Foliar Application of Nano-Fertilizers ( Macro- and Micro) Nutrients on growth , Flowering and Bulbs Yield of Yellow Iris (Iris pseudacorus L.): Pengaruh Aplikasi Daun Pupuk Nano (Makro dan Mikro) terhadap Pertumbuhan, Pembungaan, dan Hasil Umbi Iris Kuning (Iris pseudacorus L.) - Kefaia Ghazi Saeed Al-Saad; Ahmed Mohammed Ahmed Alkarkookli (Academia Open, 2026)
General Background The integration of nanotechnology into agriculture has introduced new fertilization strategies aimed at improving nutrient availability and crop productivity. Specific Background Ornamental bulbous plants such as Iris pseudacorus L. require balanced macro- and micro-nutrient supply to support flowering performance and bulb development. Knowledge Gap Despite increasing attention to nanofertilizers in horticulture, limited experimental information is available regarding the response of yellow iris to foliar applications of macro- and micronutrient nano-fertilizers at different concentrations. Aims This study evaluated the response of yellow iris to foliar spraying of nano-fertilizer containing macro- and micro-nutrients at concentrations of 0, 1, 2, 3, and 4 g L⁻¹ under a randomized complete block design with three replicates. Results The findings showed that nano-fertilizer treatments did not significantly change most vegetative growth traits. However, application at 4 g L⁻¹ accelerated flowering to 138 days and increased flower longevity to 15 days. The same treatment also produced higher bulb and bulblet formation with averages of 2.43 bulbs and 8.45 bulblets per plant, accompanied by increases in fresh bulb weight, bulblet weight, and bulb diameter. Novelty The study provides experimental evidence describing concentration-specific responses of yellow iris to foliar nano-fertilizer applications in relation to flowering behavior and bulb productivity. Implications These findings support the use of nano-fertilizer foliar spraying as a promising approach for improving reproductive performance and propagation capacity of ornamental iris cultivation. Keywords: Nano Fertilizer, Iris Pseudacorus, Foliar Application, Flowering Traits, Bulb Yield Key Findings Highlights Foliar nano-nutrient treatment accelerated flowering time in yellow iris plants Higher concentrations produced greater bulb and bulblet formation Flower longevity increased under optimized nano-fertilizer spraying